2012
DOI: 10.1002/trtr.01072
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Limited and Narrow Exposure to Informational Text

Abstract: Despite arguments for more fully including informational text in early childhood classrooms, research suggests that young children's exposure to the genre is quite limited. This article focuses on the informational books that children do encounter, specifically through read‐alouds, and describes the narrow focus of those books. Informational read‐alouds are overwhelmingly on topics of life science. The authors advocate for both increasing and broadening the informational books read aloud to young children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 26 publications
0
37
0
13
Order By: Relevance
“…As the teacher introduces the content of the book, utilizing props related to the book assists children in identifying and understanding the concepts and vocabulary contained in the material. Also necessary in the book introduction is a focus on previewing the book and drawing attention to images or features of the book in order to pique the children's interest or prompt their thinking about the topic (Yopp & Yopp, 2012). For optimal interaction, it is important for teachers to invite conversations during the reading process through routines such as "turn and talk" in which students respond to a question by turning and talking to a neighboring child during the reading experience.…”
Section: Read-aloud Routinesmentioning
confidence: 99%
See 2 more Smart Citations
“…As the teacher introduces the content of the book, utilizing props related to the book assists children in identifying and understanding the concepts and vocabulary contained in the material. Also necessary in the book introduction is a focus on previewing the book and drawing attention to images or features of the book in order to pique the children's interest or prompt their thinking about the topic (Yopp & Yopp, 2012). For optimal interaction, it is important for teachers to invite conversations during the reading process through routines such as "turn and talk" in which students respond to a question by turning and talking to a neighboring child during the reading experience.…”
Section: Read-aloud Routinesmentioning
confidence: 99%
“…In addition, follow up discussions using the vocabulary of the text is important. These discussions serve to further connect children's previous knowledge and experiences to the new information gleaned from the text (Yopp & Yopp, 2012).…”
Section: Read-aloud Routinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Il n'est donc pas surprenant que de plus en plus d'enseignants optent pour ce soutien à l'enseignement qui offre de multiples possibilités pédagogiques dans plusieurs matières scolaires. Or, bien que l'on puisse se réjouir de l'espace grandissant qu'occupe la littérature jeunesse dans les salles de classe, des chercheurs déplorent le fait que l'on n'offre pas suffisamment aux élèves du préscolaire et du primaire l'opportunité de se familiariser avec les divers genres de textes, notamment les textes informatifs (Gagnon et Ziarko, 2011 ;Ness, 2011 ;Pentimonti, Zucker, Justice et Kaderavek, 2010 ;Yopp et Yopp, 2012). En effet, cette situation est préoccupante, puisque les élèves sont appelés à lire des textes informatifs dont la complexité augmente graduellement d'un niveau scolaire à l'autre.…”
Section: Introduction Et Problématiqueunclassified
“…Yopp and Yopp, (2012) found that "exposure to informational texts in the early years is crucial if students are to succeed in a world that demands the ability to navigate the genres that dominate the later years of schooling and adulthood. "…”
Section: Informational Text In Schoolmentioning
confidence: 99%